COVID-19-related arterio-ureteral fistula formation in a post-transplant patient - Adam L. Richardson, DO; Olivia K. Richardson, MD, PharmD; Nikolas J. Touloumes, DO; Nana Y. Ohene Baah, MD (Radiology Case Reports, 2023)
Arterio-ureteral fistulas (AUF) are extremely rare and are not commonly suspected in the setting of patients with post-renal allograft transplantation. The diagnosis, while uncommon, can be potentially lethal which is only exacerbated by the clinical conundrum associated with their under-recognition and various treatment algorithms. This case identifies a unique patient with a history of 2 failed renal transplants who presents with new onset intermittent hematuria after contracting coronavirus disease 2019 (COVID-19). Despite the patient having his second renal transplant graft embolized, the patient continued to present with refractory hematuria, leading to the realization and identification of an AUF to his right renal graft. This sequence of events brings forth a case of unique significance, underscoring the potential ramifications that COVID-19 poses to the renal transplant population.